2012
DOI: 10.4103/0976-9234.99665
|View full text |Cite
|
Sign up to set email alerts
|

Insignificant antimicrobial activities and phytochemical screening in different extracts of indian Ginseng

Abstract: Aim:The aim of present study is to investigate the antimicrobial activity of (Flower, Ripen fruit and calyx) of Withania somnifera (RUBL20668) extracts, in order to use them as a possible source of new antimicrobial substances against important human pathogens. Materials and Methods: Crude extracts of different parts of both species of W. somnifera were evaluated against some important bacteria (two Gram +ve and four Gram-ve bacteria). Staphylococcus aureus (Gram +ve), Bacillus Subtilis (Gram +ve), Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“… W. somnifera has been demonstrated to have potent antiinflammatory effects in a range of medical disorders. In cases of IBD brought on by TNBS, its root extract is anti-inflammatory and restores mucous membranes resolving necrosis, edoema, and neutrophil infiltration, as well as reversing the progression of the disease 69 . In a mouse model of lupus, researchers found that a powder prepared from the roots of this plant significantly reduced inflammation as measured by proteinuria, nephritis, interleukin (IL)-6, tumour Nitric oxide (NO), reactive oxygen species (ROS), and necrosis factor-alpha 70 .…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“… W. somnifera has been demonstrated to have potent antiinflammatory effects in a range of medical disorders. In cases of IBD brought on by TNBS, its root extract is anti-inflammatory and restores mucous membranes resolving necrosis, edoema, and neutrophil infiltration, as well as reversing the progression of the disease 69 . In a mouse model of lupus, researchers found that a powder prepared from the roots of this plant significantly reduced inflammation as measured by proteinuria, nephritis, interleukin (IL)-6, tumour Nitric oxide (NO), reactive oxygen species (ROS), and necrosis factor-alpha 70 .…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The collected plant materials were shade dried till constant weight was achieved 9 . The plant material were powered with the help of grinder 10 and passed through 40mm meshes and stored in clean container for further use 11 . The dried powder material was extracted with methanol by using the Soxhlet apparatus 12 for 18 hours at a temperature not exceeding the boiling point of the respective solvent 13,14 .…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
“…The collected plant materials were shade dried, powered with the help of grinder (Singariya et al, 2012m) and passed through 40mm meshes and stored in clean container for further use (Singariya et al, 2012o). The dried powder material was extracted with acetone by using the Soxhlet apparatus (Subramanian and Nagarajan, 1969) for 18 hours at a temperature not exceeding the boiling point of the respective solvent (Singariya et al, 2013b; Singariya et al, 2012k).…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%